Blood hsCRP And PGE2 Content With Clinical Outcome Using Modified Fenestratio-Restorative Spinoplasty Better Than Lamonectomy-Fusion In Lumbar Stenosis - Mahadewa, T. B. G.; -, Sri-Maliawan; Raka-Sudewi, A. A.; Wiryana, M (BALI MEDICAL JOURNAL, 2013)
Objective: Modified Fenestration-Restorative Spinoplasty (MFRS) technique is an alternative to lumbar stenosis treatment, providing the equal decompression comparing with laminectomy techniques, without the implant, less expensive and complication rates. The purpose of this study was to determine which technique gives better inflammation and clinical outcome based on high sensitive C-Reactive Protein biomarker (hsCRP) and Prostaglandin E 2 (PGE 2 ), Visual Analog Scale (VAS) of the day 7 th postsurgery and ODI scores 3 rd month post surgery. Methods : This study design is an experimental pretest-posttest randomized control group design. Results :  This study results showed that the mean levels of hsCRP day 7 th postsurgery were differ significantly between MFRS (23,09 ± 15,3 mg/L) compared to LF (39,53 ± 24,4 mg/L). Likewise for the mean levels of PGE 2 day 7 th postsurgery were differ significantly between MFRS (491,39 ± 528,5 pg/ml) compared to LF (1103,7 ± 1033,6 pg/ml) at the significance level of p <0.05). MFRS clinical outcomes better than LF (p <0.05), for means of VAS value day 7 th postsurgery and ODI score 3 rd month postsurgery. Perioperative variable analysis shows that MFRS was better than LF in: length of surgery, blood loss, postsurgery Hb and patient length of stay (p<0,05). Conclusions: MFRS technique is an alternative technique of lumbar stenosis treatment better than the LF, in terms of improved levels of hsCRP and PGE2, leading to faster clinical outcomes improvement, less complications and lower costs. MFRS technique should be used as a treatment of lumbar stenosis.
Keywords: lumbar stenosis, inflammatory biomarker, clinical outcome, MFRS and LF.